Strategi Guru dalam Mengembangkan Sosial Emosional Anak Usia Dini - Ramadan, Syahru (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2024)
Social-emotional is one of the important aspects should be developed in children from an early age. This is because the development of social-emotional will impact much on their further development. This development can be started from children of 5-6 years old. This research aims at exploring the teacher strategies in developing social-emotional of the students. This belongs to qualitative descriptive research. The data were collected through the use of observation and interviews at Al-Mubarak Kindergarten and Islamic-Integrated Kindergarten of Ash-Shiddiq, Bone Regency. They were then processed in three stages of analysis, namely data reduction, data display, and verification or conclusion. The results reveal that teacher used various strategies in developing social-emotional of the students, including: a) rapport, positive reinforcement, and matching and mirroring in the realm of self-awareness; b) advice and appreciation in the form of positive affirmations in the realm of responsible attitudes; and c) direct direction and practical learning in the realm of prosocial behavior. These strategies can be modeled and developed again by parents and other teachers.